Examination of indigenous microalgal species for maximal protein synthesis - Tan, C.H. (Elsevier B.V., 2020)
The expanding aquaculture industry increases the prices of fishmeal, the main protein source in fish diet. A promising alternative is microalgal protein. Therefore, we investigated the protein production capacities of green microalgae Chlorella sorokiniana CY1 and Chlorella vulgaris ESP-31. After optimization, the maximum biomass and protein productivities of Chlorella sorokiniana CY1 reached high values of 4.35 ± 0.09 and 0.856 ± 0.025 g/L/d, while that of Chlorella vulgaris ESP-31 also reached high values of 4.636 ± 0.10 and 0.946 ± 0.065 g/L/d. The cultivation time for both species was only 2 days, wherein Chlorella sorokiniana CY1 and Chlorella vulgaris ESP-31 amassed moderate protein contents of 25.9 ± 1.3 and 26.8 ± 1.3. The optimum conditions for both species were 50 initial nitrate concentration of Basal medium, 5 CO2 aeration, and 750 μmol/m2/s light intensity. The high biomass and protein productivities of both species indicated their capability as potential protein sources. © 2019 Elsevier B.V.